Stochastic Distribution Controller for Wind Turbines with Doubly Fed Induction Generator - Munisamy, Vijayalaxmi; Vadivoo, Nayagam Shanmuga; Devasena, Vaithilingam (Distributed Generation & Alternative Energy Journal, 2021)
The major purpose of this work is to design the controllers for controlling the variable speed, variable pitch wind turbine (WT) with doubly fed induction generator (DFIG). Vector control strategy is adopted for controlling the DFIG active and reactive power. Generator torque is control to provide the regulated real power with minimum fluctuation. The fixed gain proportional- integral (PI) controller designed to the converter of rotor side and grid side has limited operating range and inherent overshoot. Gain scheduling PI controller is designed to minimize the overshoot and fluctuation exists in proportional-integral controller. Since DFIG based wind energy conver- sion system (WECS) works in uncertain wind speed, stochastic distribution control (SDC) method is proposed to control the probability distribution function (PDF) of DFIG based WECS. It copes with nonlinearities in the WECS and contiguous variations at operating point and provides satisfactory performance for the whole operating region. It improves the performance together with power quality of generated electric power thereby maximizing the lifespan of installation and ensures secure and acceptable operation of the DFIG based WECS.